Kinetics of the thermal dehydration of acid-activated montmorillonite by the rising temperature technique - Güler, Çetin; SARIER, NİHAL (My University, 1990)
The activation energies of dehydration and combustion of organic materials in a clay sample, and of dehydration of natural and acid-activated montmorillonite have been determined using a rising temperature programme technique. The effect of acid activation of the montmorillonite on the dehydroxylation is discussed.